Guiding principles in developing Shari'ah governance framework for Islamic capital market - Hassan, Rusni; Salman, Syed Ahmed (Serials Publications, 2017)
Shari’ah compliance is the foundation of the Islamic financial markets, including Islamic capital market. From the beginning, the Islamic capital market (ICM) was developed to support the other two Islamic financial markets such as Islamic Banking and Takaful. Later on, it became the investment avenue for investors looking for Shari’ah compliant investment and financing. Presently, the Shari’ah governance framework and regulations have been implemented for Islamic banks and Takaful. On the contrary, there is lack of similar framework of Shari’ah Governance for the Islamic capital market. Malaysia having positioned itself as a hub of Islamic finance should introduce a Shari’ah governance framework for the Islamic capital market. Thus, the objective of this paper is to provide the principles on which the theoretical Shari’ah governance framework for the Islamic capital market can be developed. These principles are Islamic accountability and responsibility, independence and objectivity, competence, confidentiality and commitment, consistency, Shari’ah audit and review, transparency and disclosure, corporate social responsibility and ethicality. In addition, this paper discusses the Shari’ah governance practices in Indonesia, Bahrain, Pakistan, Kuwait and Malaysia. This write-up will be of interest to individual players, regulators, investors and the public.